Reforming the international financial system for effective aid delivery - Ikhide, Sylvanus (2004)
Focuses on the reform of the development finance institutions to enable them to discharge their development goal. Reviews the lessons learnt from international experiences in development finance from the particular perspective of developing economies whose growth and stability depend to a large extent on the availability of long-term external finance